A new eosinophilic esophagitis (EoE)‐like disease without tissue eosinophilia found in EoE families. Issue 6 (1st April 2016) - Straumann, A.; Blanchard, C.; Radonjic‐Hoesli, S.; Bussmann, Ch.; Hruz, P.; Safroneeva, E.; Simon, D.; Schoepfer, A. M.; Simon, H.‐U.
Abstract: Background: Eosinophilic esophagitis (EoE) is a rapidly emerging, chronic inflammatory, genetically impacted disease of the esophagus, defined clinically by symptoms of esophageal dysfunction and, pathologically, by an eosinophil‐predominant tissue infiltration. However, in four EoE families, we have identified patients presenting with EoE‐typical and corticosteroid‐responsive symptoms, but without tissue eosinophilia. The aim of this study was to clinically and immunologically characterize these patients with EoE‐like disease. Methods: Five patients suffering from an EoE‐like disease were evaluated with endoscopic, histologic, functional, and quantitative immunohistological examinations, and mRNA expression determination. Results: The frequency of first‐generation offspring of patients affected by EoE or EoE‐like disease was 40%. Immunofluorescence analysis confirmed an almost complete absence of eosinophils in the esophageal tissues of patients with EoE‐like disease, but revealed a considerable T‐cell infiltration, comparable to EoE. In contrast to EoE, eotaxin‐3 mRNA and protein were markedly reduced in EoE‐like disease ( P < 0.05). The mRNA expression levels of three selected EoE genes ( eotaxin‐3, MUC4, and CDH26 ) allowed to discriminate between EoE‐like disease, EoE, and normal epithelium. Conclusions: Patients suffering from 'EoE without eosinophilia' do not fulfill formally the diagnostic criteria for EoE. However, their clinical manifestation, immunohistology, and gene expression pattern, plus the fact that they bequeath EoE to their offspring, suggest a uniform underlying pathogenesis. Conventional EoE, with its prominent eosinophilia, therefore appears to be only one phenotype of a broader 'inflammatory dysphagia syndrome' spectrum. In this light, the role of the eosinophils, the definition of EoE, and its diagnostic criteria must likely be reconsidered.